COMPETITIVENESS ANALYSIS OF INDONESIAN COFFEE IN THE GERMANY AND JAPAN - I Nyoman Astawiguna; Ambya; Ida Budiarty (ZILLZELL MEDIA PRIMA, 2025)
Coffee farming commodities are one of Indonesia's leading export commodities to various coffee-importing countries in the world and contribute to the country's foreign exchange. Indonesia is the fourth largest coffee producer in the world after Brazil, Vietnam and Colombia. The five countries that are the main export destinations for Indonesian coffee beans (HS code 090111) are the United States, Germany, Japan, Italy, and Malaysia, however, the average export of Indonesian coffee to Germany and Japan shows an expected decline due to the low competitiveness of Indonesian coffee exports. The purpose of the study was to analyze Indonesian coffee exports to Germany and Japan. The data used by the value panel (US Dollar) is from the Central Statistics Agency (BPS), Trade MAP and UN Comtrade for the 2014-2023 period. The analysis method uses Revealed Competitive Advantage (RCA) which has a value of > 1 and the method is refined with Revealed Symmetric Comparative Advantage (RSCA) which has < values of 0 and > 0. The results of the study found that Indonesian coffee exports in Germany and Japan have strong competitiveness in the German market, but compared to Brazil, Vietnam, Colombia, Guatemala, Indonesia's RSCA value in the German and Japanese markets is far behind. Therefore, it is necessary to increase the volume of coffee exports to the German and Japanese markets in a sustainable manner